2018
DOI: 10.1007/s12053-018-9643-7
|View full text |Cite
|
Sign up to set email alerts
|

Solar heat gains through train windows: a non-negligible contribution to the energy balance

Abstract: The sector of transportation accounts for about one third of the total energy consumption in Switzerland. A monitoring campaign of the energy consumption of a regional train revealed the critical energyconsuming systems. Heating, cooling and ventilation were identified as major consumers. Windows are a source of non-controlled heat transfer. In summer, it may result in overheating leading to larger cooling loads while in winter, it is an important source of thermal losses. Selective double glazing and solar pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A study focused on the transparent portion of the envelope has been reported by Bouvard et al [6], where the impact of the solar gains on the HVAC energy consumption of a panoramic train (large windows) has been investigated. They showed that the incoming energy due to the solar gains is in the same order of magnitude as required for the heating or cooling systems, and that an appropriate choice of the glazing can lead to energy savings of 7 to 13%, depending on the climate.…”
Section: Local Interior Airmentioning
confidence: 99%
“…A study focused on the transparent portion of the envelope has been reported by Bouvard et al [6], where the impact of the solar gains on the HVAC energy consumption of a panoramic train (large windows) has been investigated. They showed that the incoming energy due to the solar gains is in the same order of magnitude as required for the heating or cooling systems, and that an appropriate choice of the glazing can lead to energy savings of 7 to 13%, depending on the climate.…”
Section: Local Interior Airmentioning
confidence: 99%
“…As such they require mechanical cooling (air conditioning) and ventilation. This, however, consumes a considerable amount of energy, [131] with the result that manufacturers and operators tend to recirculate most of the air and minimise the amount of 'fresh' outdoor air that is supplied to the carriages. [132] CO2 concentrations >1 800 ppm [132][133][134] and as high as 5 525 ppm [135] have been recorded on urban railway carriages during peak periods (CO2 concentrations in well-ventilated spaces are generally <1 000 ppm).…”
Section: Scenariomentioning
confidence: 99%
“…In 2018, Bouvard [21] from Switzerland estimated the solar heat gains through train windows; the result shows a 7–13% energy savings from using glazing adapted to the climatic conditions. Solar gains play a non‐negligible role in the energy balance of the wagon.…”
Section: Literature Reviewmentioning
confidence: 99%